Fiscal decentralization and corruption: The moderating role of economic responsibility audit in China - Fang, Chen Ji; Ahmi, Aidi; Sharif, Zakiyah (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to assess the effectiveness of the Economic Responsibility Audit (ERA) system in mitigating corruption associated with fiscal decentralization in China. Using data from 30 provinces in China between 2010 and 2021, this study examines the impact of income and expenditure decentralization on corruption levels. The study employs statistical models to explore the relationships between fiscal decentralization and corruption, as well as the moderating effect of the ERA system. The analysis reveals that both income decentralization and expenditure decentralization are positively and significantly correlated with increased corruption levels. Notably, expenditure decentralization has a stronger and more pronounced effect on corruption compared to income decentralization. Additionally, the ERA system does not moderate or reduce the positive relationship between fiscal decentralization and corruption. The findings suggest that the ERA system is limited in its capacity to curb corruption in the context of fiscal decentralization. Despite the audit system’s implementation, it does not appear to effectively address the link between decentralization and corruption, particularly regarding expenditure decentralization. These results provide critical insights for policymakers and governance officials, indicating the need for stronger and more targeted anti-corruption strategies. The study suggests reconsidering the effectiveness of the ERA and exploring complementary mechanisms to reduce corruption in the decentralized fiscal system.